Single‐cell transcriptomics uncovers an instructive T‐cell receptor role in adult γδ T‐cell lineage commitment - Scaramuzzino, Sara; Potier, Delphine; Ordioni, Robin; Grenot, Pierre; Payet‐Bornet, Dominique; Luche, Hervé; Malissen, Bernard (The EMBO journal, 2022)
After entering the adult thymus, bipotent T‐cell progenitors give rise to αβ or γδ T cells. To determine whether the γδ T‐cell receptor (TCR) has an instructive role in γδ T‐cell lineage commitment or only “confirms” a pre‐established γδ Τ‐cell lineage state, we exploited mice lacking expression of LAT, an adaptor required for γδ TCR signaling. Although these mice showed a T‐cell development block at the CD4 − CD8 − double‐negative third (DN3) stage, 0.3% of their DN3 cells expressed intermediate levels of γδ TCR (further referred to as γδ int ) at their surface. Single‐cell transcriptomics of LAT‐deficient DN3 γδ int cells demonstrated no sign of commitment to the γδ T‐cell lineage, apart from γδ TCR expression. Although the lack of LAT is thought to tightly block DN3 cell development, we unexpectedly found that 25% of LAT‐deficient DN3 γδ int cells were actively proliferating and progressed up to the DN4 stage. However, even those cells failed to turn on the transcriptional program associated with the γδ T‐cell lineage. Therefore, the γδ TCR‐LAT signaling axis builds upon a γδ T‐cell uncommitted lineage state to fully instruct adult γδ T‐cell lineage specification. Synopsis After entering the adult thymus, bipotent T‐cell progenitors give rise to αβ or γδ T cells. Single‐cell resolution analyses of mice lacking the LAT adaptor reveal that the γδ T‐cell receptor (TCR) signaling exerts a key inductive role in adult γδ T‐cell lineage commitment and specification. Single‐cell transcriptomics defines the expression signature for adult γδ T‐cell lineage commitment. The expression signature of γδ T‐cells in the adult thymus depends on LAT expression. γδ T‐cell specification depends on γδ TCR signaling. Adult DN3 stage can be a point of αβ versus γδ lineage bifurcation. Graphical Abstract TCR signaling via the LAT adaptor determines the developmental bifurcation of αβ and γδ T‐cell lineages in the adult mouse thymus.